2001
DOI: 10.1093/phr/116.6.568
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Interventions for the Control of Tuberculosis Among Adolescents

Abstract: SYNOPSISObjectives. Activation of latent tuberculosis infection into tuberculosis disease (TB), the primary killer among infectious diseases worldwide, can be prevented with six months of anti-TB medication. A large percentage of adolescents started on medication, however, fail to complete their treatment. The authors developed and tested the effects of innovative educational strategies on infected adolescents at two health centers serving ethnically diverse populations.Methods. The authors used a randomized e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 10 publications
0
37
0
Order By: Relevance
“…The adolescent's family was also involved as active participants of the intervention, above and beyond providing consent, in seven studies [38,41,[45][46][47][48][49]. In all, 12 of the AEI studies were conducted in the United States [38 -49] and 10 of the interventions involved adolescents with type 1 diabetes mellitus (T1DM) [38 -41,46 -50,53].…”
Section: Study Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adolescent's family was also involved as active participants of the intervention, above and beyond providing consent, in seven studies [38,41,[45][46][47][48][49]. In all, 12 of the AEI studies were conducted in the United States [38 -49] and 10 of the interventions involved adolescents with type 1 diabetes mellitus (T1DM) [38 -41,46 -50,53].…”
Section: Study Participantsmentioning
confidence: 99%
“…Alternative delivery sites, used alone or in addition to the clinic, included the patients' homes [41,43,45,46,50], schools [52], and in four cases, various venues including community facilities were considered [40,41,43,46]. One intervention was based on text messaging [53].…”
Section: Intervention Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Hovell et al 62 Dick et al 42 Subtotal Subtotal Demissie et al 67 Alvarez-Gordillo et al 66 Case-control Barnwell et al 38 Intervention White et al 58 Chaisson et al 52 Morisky et al 56 Subtotal …”
Section: Cohortmentioning
confidence: 99%
“…261 A six-month American study found that peer counselling for adolescents did not have an effect on self-reported treatment completion rates. 262 Peer support group therapy for adolescents with HIV showed no change in adherence, according to physician reports. 263 A five-month clinic-wide social marketing campaign was conducted to improve adherence to antiretroviral therapy.…”
Section: Social Support Interventionsmentioning
confidence: 99%